2019
DOI: 10.9734/cjast/2019/v33i630107
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-related Post-harvest Physiological Disorders of Fruits and Vegetables in Eswatini: A Review

Abstract: Calcium (Ca2+) related physiological disorders of fruits and vegetables are abnormalities of fruits and vegetables which are not caused by infectious diseases, insects, nematodes or animals. Fruit and vegetable abnormalities occur due to environmental stress, nutritional deficiencies or excess on the plant. In this study, information was sought through informal surveys, review of literature and interviews with key post-harvest handling and storage participants and direct observation of fruits and vegetables in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The delayed softening observed here could be attributable to the higher calcium level in fruit tissue, in addition to the advantage of calcium ascorbate in preventing browning. Calcium (Ca 2+ ) is an important mineral for fruit as it helps to maintain cell wall integrity and fruit quality [36]. While suppressing polygalacturonase (PG) activity, the production of calcium pectates and membrane system stability improved the stiffness of the middle lamella and cell walls [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The delayed softening observed here could be attributable to the higher calcium level in fruit tissue, in addition to the advantage of calcium ascorbate in preventing browning. Calcium (Ca 2+ ) is an important mineral for fruit as it helps to maintain cell wall integrity and fruit quality [36]. While suppressing polygalacturonase (PG) activity, the production of calcium pectates and membrane system stability improved the stiffness of the middle lamella and cell walls [11].…”
Section: Resultsmentioning
confidence: 99%
“…At this stage and until seven days of storage, the ASC treated fre cut slices kept the highest firmness values. However, 12 days after storage, the firmn of both the ASC treatment and the untreated fruit dropped to the lowest values (Figu and fruit quality [36]. While suppressing polygalacturonase (PG) activity, the prod of calcium pectates and membrane system stability improved the stiffness of the lamella and cell walls [11].…”
Section: Resultsmentioning
confidence: 99%
“…is means that the enzyme activities are higher in granulated fruits as compared with those in the healthy fruits. Wenqin [21] Adverse atmospheric condition: cold weather during the maturity period [5,20] Sink competition among the different plant parts, i.e., fruits, roots, and leaves.…”
Section: Effects Of Granulation On Reactive Oxide Species and Othermentioning
confidence: 99%
“…[9, 22, 23] Rootstocks and cultivars type [3,24] Higher water potential in juice cells [25] High temperatures during flowering and fruit set [12] Calcium deficiency [20] Enzymes activity: polyphenol oxidase (PPO), peroxidase (POD), superoxide dismutase (SOD), catalase (CAT), pectinmethylesterase (PME), and cellulose [26] et al [26] have also reported that the inbred pumelo fruits have higher granulation than hybridized fruits. Researchers also noted that no new isoenzymes appear when both inbred and hybridized pumelo fruits are granulated.…”
Section: Effects Of Granulation On Reactive Oxide Species and Othermentioning
confidence: 99%
See 1 more Smart Citation